Dissenting Opinion Hakim Dalam Perkara Pembatalan Hibah di Pengadilan Agama Gorontalo - Astuti Lauris; Nur Mohamad Kasim; Suwitno Yutye Imran (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to find out and analyze whether the judge's dissenting opinion in case No.0687/Pdt.G/2017/PA.Gtlo regarding the cancellation of this grant provides justice for the parties. The method used in this research is normative juridical with a statutory approach (statute aproach) and a case approach (case aoprouch). The results of this research show that dissenting opinions provide justice for the parties because having a dissenting opinion provides something that is really needed by the parties where the parties feel that their arguments are heard and considered and not set aside by the panel of judges.